Vitamin D receptor (VDR) gene polymorphisms and expression profile influence upon the immunological imbalance in Turner syndrome - Santos, L O; Laranjeira, R; Borborema, M E B de A; Sotero-Caio, C G; Duarte, A de R; Araújo, J; de Azevedo Silva, J; Santos, N (Journal of endocrinological investigation, 2020)
PURPOSE: Turner syndrome (TS) patients display considerable immune misregulation, and it is hypothesized that Vitamin D (VTD) activity may fluctuate according to Vitamin D receptor (VDR) polymorphisms and/or expression profile. To uncover a possible relationship between VDR genotype and clinical conditions in TS patients, we investigated two functional VDR variants (Cdx-2 and FokI) for allele and genotype frequencies, as well as expression profile in TS individuals versus healthy controls (HC). METHODS: We performed a genetic association study including 100 TS patients and 116 HC. Genotyping for VDR Cdx-2 G > A (rs11568820) and FokI C > T (rs2228570) was performed using Taqman Genotyping Assays. VDR gene expression was also evaluated in 15 TS and 15 HC, using fluorogenic probes by qPCR. Statistical analyses were performed using nonparametric Mann-Whitney test, with a 5% significance level (p < 0.05) to uncover differences between groups. In addition, we investigated whether shifted VDR mRNA levels were associated with Cdx-2 and FokI variants in TS patients. RESULTS: We detected a significantly higher frequency of T allele (p = 0.006) as well as T/T genotype (p = 0.01) for FokI in TS patients when compared to HC. When assessing VDR expression, we identified a downregulation in TS woman (- 2.84 FC) versus HC (p < 0.001). Furthermore, C/T (11.24 FC; p = 0.01) and T/T (9.20 FC; p = 0.01) FokI genotypes were upregulated when compared to C/C reference genotype. CONCLUSION: TS patients show different distribution of FokI polymorphism. Downregulation of VDR gene expression may contribute to immunological imbalance in TS.
Keywords: dospělí; Genotype; Female; Infant; Autoimmunity; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; jednonukleotidový polymorfismus; Adolescent; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; Turnerův syndrom; studie případů a kontrol; frekvence genu; Receptors, Calcitriol; Down-Regulation; genetické asociační studie; Case-Control Studies; kojenec; Child, Preschool; Young Adult; Genetic Association Studies; alely; autoimunita; Alleles; Turner Syndrome; Child; down regulace; mladiství; receptory kalcitriolu; Humans